Effect of Surface Tension on Hydrodynamics and Mass Transfer Coefficient in Airlift Reactors. Issue 5 (7th February 2020) - Kumar, Nikesh; Gupta, Renu; Bansal, Ajay
Abstract: The hydrodynamics and volumetric mass transfer coefficient play important roles in the design and scale‐up of airlift reactors. The effect of surface tension on hydrodynamics and volumetric mass transfer coefficient in internal loop airlift reactors was investigated. With reduction of the surface tension of the fluid, the hydrodynamic parameters raised, namely, gas phase holdup, flow regime transition point, and interfacial area, whereas the bubble diameter as well as the liquid velocity decreased and the volumetric mass transfer coefficient increased. Empirical correlations are proposed for gas‐phase holdup and volumetric mass transfer coefficient in terms of dimensionless numbers and can be applied in the design of airlift reactors. Abstract : The surface tension influences hydrodynamics parameters as well as the volumetric mass transfer coefficient and consequently the performance of airlift reactors. The gas‐phase holdup and volumetric mass transfer coefficient correlated empirically in terms of dimensionless numbers and can be applied to evaluate these parameters for similar types of reactors.